2018
DOI: 10.1021/acsomega.7b01316
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Properties of Nanocrystalline TiO2 with Multiwalled Carbon Nanotubes and Its Photovoltaic Studies Using Ru(II) Sensitizers

Abstract: In this study, the in situ sol–gel method has been deployed to prepare the titanium dioxide/multiwalled carbon nanotubes (TiO 2 /MWCNTs) nanocomposite (NCs) powders with varying content of MWCNTs (0.01–1.0 wt %), to construct the dye-sensitized solar cells (DSSCs). First, binder-free NCs were deposited on a transparent-conducting F:SnO 2 (FTO) glass substrate by a doctor-blade technique and then anchored with Ru(II)-based dyes to either N719 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 51 publications
5
44
0
Order By: Relevance
“…The anti-microbial activity result is phographically represented in Figure 7,respectively. Meanwhile, the remarkable, resistance for antibiotic is observed due to poor antibiotic penetration and adaptive bacterial response[33][34]. This increases the need of finding new antibiotic which has been fulfilled by making composite of different nanoparticle composite with various concentrations.…”
mentioning
confidence: 99%
“…The anti-microbial activity result is phographically represented in Figure 7,respectively. Meanwhile, the remarkable, resistance for antibiotic is observed due to poor antibiotic penetration and adaptive bacterial response[33][34]. This increases the need of finding new antibiotic which has been fulfilled by making composite of different nanoparticle composite with various concentrations.…”
mentioning
confidence: 99%
“…49 While, in case of NZC NCs the characteristics XRD reections of the ZnO NPs are retained in NCs at their respective 2q values; without characteristics reections corresponds to MWCNTs due to their less content or lower concentration of MWCNTs in the NCs and which could not be traced out by the XRD. 44 In addition the close assessment of XRD patterns indicates that the intensity of XRD reections are decreases signicantly aer forming NCs with MWCNTs upto NZC 0.1 NCs to that of undoped ZnO NPs. In case of 5 NZ the intensity of XRD reections drastically reduced which is reported earlier 49,50 and if consider NZC NCs only, intensity of XRD pattern reections is enhanced signicantly from NZC 0.01 to NZC 0.05 NCs and…”
Section: X-ray Diffraction Analysismentioning
confidence: 95%
“…51 The frequency region at 3000-3500 cm À1 corresponds due to the -OH functional moieties present in 5 NZ and NZC NCs. 44,52 In 5 NZ , sharp stretching bands observed at 830 cm À1 , 51 1066 cm À1 and 1378 cm À1 corresponding to the Zn-O-Ni bonding, Ni 2+ ions occupies Zn 2+ sites of host lattice of ZnO NPs and presence of NO 3 . 53,54 The shi of stretching vibration frequencies of 5 NZ and NZC NCs as compare to undoped ZnO NPs with supporting of respective sharp stretching bands indicates the substitution of Ni 2+ ions in Zn 2+ sites of host lattice of ZnO NPs.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in comparison to bare TiO 2 or binary composites (TiO 2 /RGO and TiO 2 /CNTs), the optoelectronic and photovoltaic studies of (Mo x Ti 1‐2x O 2‐δ ) 1‐y (RGO) y is still obscure. Along with preferable dopant, the carbon nanostructures (CNTs or RGOs) are also used as supportive materials due to having ability to boost the properties of host materials for energy harvesting studies . Recently, our research group studied the binary TiO 2 /RGO NCs based DSSCs and reported the highest power conversion efficiencies of η=5.98% and η=4.76% for optimized TiO 2 /RGO (0.75 wt.%) composites sensitized with N719 and N3 dyes, respectively .…”
Section: Introductionmentioning
confidence: 91%